Global deletion of COX-2 attenuates hepatic inflammation but impairs metabolic homeostasis in diet-induced obesity - Jeyakumar Balakrishnan; Cyrus Desouza; Rishikesh Thakare; Yazen Alnouti; Viswanathan Saraswathi (Journal of Lipid Research)
The role of cyclooxygenase-2 (COX-2), a well-known pharmacological target for attenuating inflammation, in regulating obesity and its comorbidities remains unclear. We sought to determine the role of COX-2 in modulating metabolic inflammation and systemic metabolic homeostasis in obesity. Male WT and COX-2 KO mice were fed a chow diet or a high fat diet (HF, 45% fat) for 13 weeks. While the body weight gain did not alter, the visceral adipose tissue mass was significantly higher in KO-HF mice than in WT-HF mice. Plasma triglycerides and total cholesterol levels were higher in KO-HF mice than in WT-HF mice. Total body fat mass was higher with a concomitant reduction in lean mass in KO-HF mice than in WT-HF mice. Paradoxically, hepatic steatosis was reduced in KO-HF mice. While liver triglycerides were reduced, the liver cholesterol was increased in KO-HF mice. Bile acids and markers of cholesterol biosynthesis were unaltered between WT-HF and KO-HF groups. The mRNA and/or protein levels of autophagy markers were significantly decreased in KO-HF mice compared to WT-HF mice, indicating that a reduction in autophagy may increase cholesterol levels in these mice. The liver inflammatory markers were significantly increased only in WT mice fed a HF diet but not in KO-HF fed mice compared to their respective controls. Visceral adipose tissue showed a reduction in inflammatory markers in spite of an increase in adiposity. These data suggest that despite being effective in attenuating the inflammatory processes, inhibition of COX-2 exerts undesirable consequences on metabolic homeostasis.